Preparation and characterization of oil palm empty fruit bunch-based cellulose for levulini acid production - Zulkipli, Nor Akhlisah; Wan Ab Karim Ghani, Wan Azlina; Yunus, Robiah; Yap, Taufiq Yun Hin; Rashid, Umer (Penteract Technology, 2024)
This study investigates the process of isolating and characterizing cellulose from Oil Palm Empty Fruit Bunch (OPEFB) fibers collected from Sime Darby Plantation, Selangor. The OPEFB fibers underwent a sequence of chemical processes including dewaxing, alkali pretreatment and bleaching, to isolate the cellulose. The resulting cellulose was analyzed for its composition, crystallinity and yield of hydrolysis products. Comparative analysis with recent studies indicates that the cellulose content of the isolated fibers falls within the reported range, with relatively lower lignin content suggesting a successful lignin removal during chemical treatments. The crystallinity index of the cellulose significantly increased after the post-treatment, reaching 76.43%, which is higher than some reported values. The hydrolysis of the isolated cellulose from OPEFB yielded levulinic acid (LA) levels comparable to commercial cellulose, with the OPEFB-based cellulose producing an LA yield of 8.98% lower than the 9.73% from commercial cellulose. This study highlights the potential of OPEFB as a viable source of high-quality cellulose for the production of sugars and LA